2019
DOI: 10.1093/cid/ciz1070
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Activation Markers by Mycobacterium tuberculosis-specific CD4+ T Cell Distinguishes Extrapulmonary From Pulmonary Tuberculosis and Latent Infection

Abstract: Background Diagnosis of active tuberculosis (ATB) currently relies on detection of M. tuberculosis (Mtb). Identifying patients with extrapulmonary TB (EPTB) remains challenging because microbiological confirmation is often not possible. Highly accurate blood-based tests could improve diagnosis of both EPTB and pulmonary TB (PTB), and timely initiation of anti-TB therapy. Methods A case-control study was performed using discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 20 publications
10
45
0
Order By: Relevance
“…Translation of whole blood assay-based approaches into diagnostic and treatment monitoring tools requires use of simplified flow cytometry panels. Upon focusing our analyses solely on HLA-DR expression, our data concur with previous findings from our group and others that a 4-colour panel (including CD3, CD4, IFN-c and HLA-DR) could discriminate latent from aTB 15,[18][19][20] and could also be useful to monitor the response to treatment, as recently suggested by Ahmed et al 29 Here, we show for the first time that this approach: (1) could identify those at highest risk of poor treatment outcomes, (2) could gauge the extent of TB disease severity and (3) importantly, exhibit comparable performance in HIV-infected persons, who are at highest risk of TB disease. While flow cytometry may appear complex, its usage in clinical tests is becoming more common with the availability of compact flow cytometers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Translation of whole blood assay-based approaches into diagnostic and treatment monitoring tools requires use of simplified flow cytometry panels. Upon focusing our analyses solely on HLA-DR expression, our data concur with previous findings from our group and others that a 4-colour panel (including CD3, CD4, IFN-c and HLA-DR) could discriminate latent from aTB 15,[18][19][20] and could also be useful to monitor the response to treatment, as recently suggested by Ahmed et al 29 Here, we show for the first time that this approach: (1) could identify those at highest risk of poor treatment outcomes, (2) could gauge the extent of TB disease severity and (3) importantly, exhibit comparable performance in HIV-infected persons, who are at highest risk of TB disease. While flow cytometry may appear complex, its usage in clinical tests is becoming more common with the availability of compact flow cytometers.…”
Section: Discussionsupporting
confidence: 89%
“…14 Furthermore, several studies have highlighted the potential of blood-based assays as diagnostic tools; and while measuring the magnitude of Mtb-specific T-cell response does not offer much value for TB diagnostic 15,16 or treatment monitoring, 17 assessing the phenotypic profile of these cells showed promising results. Indeed, the activation, memory differentiation or functional profile of Mtb-specific CD4 T cells has been shown to relate to TB disease activity 15,[18][19][20][21][22][23][24][25][26][27] and evaluate treatment response. 18,19,28,29 However, very few of these studies have included HIV-infected participants.…”
Section: Introductionmentioning
confidence: 99%
“…Whole blood biomarkers that can better predict the risk of TB progression are being studied using RNA sequencing of blood from cohorts; these studies are identifying gene signatures for the risk of progression to active TB (Zak et al, 2016;Wang et al, 2019;Suliman et al, 2018;Warsinske et al, 2018;Deng et al, 2019;Gupta et al, 2020). Mtb-specific CD4+ T-cell activation markers in blood may discriminate pulmonary and extrapulmonary TB from LTBI (Silveira-Mattos et al, 2019). Recently, Mtb has been demonstrated in mesenchymal and hematopoietic stem cells (Mayito et al, 2019); thus whole genome sequencing of bone marrow specimens from LTBI patients may show the presence of Mtb with rpo gene mutations in stem cell CD34 populations.…”
Section: Advancing Ltbi Diagnostic Testsmentioning
confidence: 99%
“…Expression of HLA-DR, a member of the MHC class II family typically expressed by antigen-presenting cells, is often used as a marker of T cell activation [15,16]. In the context of tuberculosis, studies have shown that disease, regardless of HIV status, is associated with significantly higher levels of T cell activation than M.tb infection, and that activation is reduced upon successful antimicrobial treatment [17][18][19][20][21][22]. These studies suggest that antigen-specific T cell activation could be used as a biomarker of microbial burden, and potentially infer in vivo antigen exposure during different stages of infection and disease.…”
Section: Introductionmentioning
confidence: 99%
“…TST and IGRAs have a low predictive value for tuberculosis [26]. Other functional assays that measure M.tbspecific T cell properties such as Th1 cytokine co-expression profiles [27,28], T cell differentiation (CD27, [29,30]) and T cell activation [17][18][19][20][21][22] have been proposed as new potential immunodiagnostic concepts that can distinguish between M.tb infection and disease. In line with this principle, potential biomarkers of recent M.tb infection based on proportions of TNF-only (IFN--IL-2-) TE (CD45RA-CCR7-CD127-) CD4 T cells or T cell proliferation, as well as a blood transcriptomic signature, have been described [31][32][33].…”
Section: Introductionmentioning
confidence: 99%